PERAN PEMERINTAH DESA DALAM MENYELESAIKAN KONFLIK LAHAN PERKEBUNAN KELAPA SAWIT - Cindy Nabilla; M. Qur’anul Kariem; Doris Febrianti (Journal of Urban Sociology, 2022)
The province of South Sumatra is one of the largest palm oil producers in Indonesia. Oil palm plantations in South Sumatra are spread over several regencies and cities, one of which is Banyuasin Regency. This potential encourages the Banyuasin district government to attract entrepreneurs to do business in the field of oil palm plantations and to build oil palm factories, especially in Gasing Village, Banyuasin Regency. On the other hand, oil palm plantation business activities in Gasing Village, Banyuasin Regency also have a negative impact, namely the occurrence of conflicts between the community and the company, namely conflicts over the legality of land ownership. The area of the problematic land is 110 hectares where there are several residents who claim that this 110 hectares of land is theirs. The method used is a qualitative research method. Data obtained through direct observation and interviews. The results show that the settlement of land disputes related to oil palm plantations has not been smooth and optimal because there are a number of obstacles although in the end it can be resolved. Recommendations from this research are socialization, creation of discussion forums on land/land protection, and education conducted by BPN. Keywords: Rolle of Village Government, Conflict, Oil Palm Plantation.